A lifeline for the subaltern: group work during the covid-19 pandemic in Jharkhand, India. Issue 1 (2nd January 2022) - Saini, Ajay
ABSTRACT: In the times of covid-19, when fear and panic have dramatically divided the society, pushing the vulnerable populations further to the margins; the pandemic response of the Van Suraksha Samiti became a lifeline for the subaltern in Jharkhand.